2021
DOI: 10.20944/preprints202107.0647.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene – Diamond Nanomaterials: A Status Quo Review

Abstract: Carbon nanomaterials with a different character of the chemical bond – graphene (sp2) and nanodiamond (sp3) are the building bricks for a new class of all-carbon hybrid nanomaterials, where the two different carbon networks with the sp3 and sp2 hybridization coexist, interact and even transform into one another. The unique electronic, mechanical, and chemical properties of the two border nanoallotropes of carbon ensure the immense application potential and versatility of these all-carbon graphene &am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 147 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…Thus, graphene(sp 2 )nanodiamond(sp 3 ) nanomaterials were investigated and their heterojunctions, composites, and other hybrids were explored for possible use in sensing, electronic, energy storage, and other applications. [75]…”
Section: Carbon Nanotubes Fullerenes and Their Hybridsmentioning
confidence: 99%
“…Thus, graphene(sp 2 )nanodiamond(sp 3 ) nanomaterials were investigated and their heterojunctions, composites, and other hybrids were explored for possible use in sensing, electronic, energy storage, and other applications. [75]…”
Section: Carbon Nanotubes Fullerenes and Their Hybridsmentioning
confidence: 99%
“…24 Previous research has investigated combining nanodiamonds with graphene or graphite for various applications. 26,27 Diamond nanoparticles have been used to enhance graphene exfoliation 28 and reduce friction. 29,30 However, there's a limited exploration of using diamond nanoparticles for graphene exfoliation or converting graphite into ND-GCSs carbon microspheres under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated combining nanodiamonds with graphene or graphite for various applications. , Diamond nanoparticles have been used to enhance graphene exfoliation and reduce friction. , However, there’s a limited exploration of using diamond nanoparticles for graphene exfoliation or converting graphite into ND-GCSs carbon microspheres under microwave irradiation. , Additionally, to the best of the authors’ knowledge, no study in the open literature has reported on the potential use of ND-Gr composites as active catalysts for the hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%